(untitled) (Journal of Management and Social Sciences, 2019)
The Niger Delta conflict is viewed as a recurrent conflict that affects many facets of Nigeria’s existence. Therefore stakeholders such as government, business organizations as well as oil-bearing communities use the mass media to promote their interest in the region. One strategy used by different groups is media framing that allows people to present events in a way that allows readers attach a particular meaning to specific contents. This study focused on the engagement of framing in newspaper coverage of conflict in the Niger Delta. The newspapers selected were Vanguard, and Champion newspapers. The study was anchored on framing theory that notes that the media not only tell us what to think about, but how to think about them. Sample size was drawn from 1998 to 2002. Findings revealed the newspapers preferred thematic to episodic frames, main sources of frames were own correspondents and government .News was used more than other editorial formats. It is germane that journalists are trained on the dynamics of framing, especially conflict and their implications on society. The mass media should also provide early warning signs that would contribute to the escalation of conflicts.